Development of calcium phosphate/calcium sulfate biphasic biomedical material with hyaluronic acid containing collagenase and simvastatin for vital pulp therapy. Issue 6 (June 2020) - Chang, Hao-Hueng; Chang, Yao-Jen; Yeh, Chun-Liang; Lin, Ting-An; Lin, Chun-Pin
Abstract: Objective: In vital pulp therapy (VPT), a barrier is created with appropriate capping to protect the remaining pulp and thus maintain pulp vitality. Here, we evaluated the feasibility of a biphasic calcium phosphate cement (CPC)–calcium sulfate hemihydrate (CSH) biomaterial containing simvastatin (Sim) and collagenase (Col) for VPT. Methods: Combinations of varying CPC and CSH concentrations were analyzed for their handling properties and setting times, with their structures observed through scanning electron microscopy–energy dispersive X-ray spectrometry (SEM-EDS). Drug release patterns of simvastatin and collagenase combined with CPC–CSH (CPC–CSH–Sim–Col) were also analyzed, followed by biocompatibility and bioactivity tests on human dental pulp stem cells (hDPSCs) and in vivo animal study in canine models; the in vivo results were obtained through microcomputed tomography and histological analysis. Results: The results revealed that 70 wt% CPC (CPC7) with 30 wt% CSH (CSH3) exhibited optimal setting time and porous structure for clinical use. The cell viability and cytotoxicity analysis demonstrated that CPC7–CSH3 with or without simvastatin or collagenase did not injure hDPSCs. In vivo, the CPC7–CSH3–Sim–Col induced dentin bridge formation. Significance: CPC7–CSH3–Sim–Col in this study has great potential as a VPT biomaterial to enhance the dentin bridge formation.